2019
DOI: 10.1039/c9dt03470f
|View full text |Cite
|
Sign up to set email alerts
|

A bis(aluminocenophane) with a short aluminum–aluminum single bond

Abstract: A bis(aluminocenophane) with a remarkably short Al–Al single bond, which was studied in detail by DFT calculations, is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
1
16
0
1
Order By: Relevance
“…reported that the C[2]aluminocenophane chloride dimer, initially reported by Shapiro et al., could be reduced using a 1,3‐diketiminate magnesium(I) reagent, to give the corresponding dialane 5 a (Scheme 10). [56] …”
Section: Metallocenophanes Of Group 13 Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that the C[2]aluminocenophane chloride dimer, initially reported by Shapiro et al., could be reduced using a 1,3‐diketiminate magnesium(I) reagent, to give the corresponding dialane 5 a (Scheme 10). [56] …”
Section: Metallocenophanes Of Group 13 Elementsmentioning
confidence: 99%
“…The quest for a" true" group 13 metallocenophane was successful, when in 2019 Schäfer et al reported that the C [2]aluminocenophane chloride dimer,i nitially reported by Shapiro et al,c ould be reduced using a1 ,3-diketiminate magnesium(I) reagent, to give the corresponding dialane 5a (Scheme 10). [56] Compound 5a is noteworthy in several regards, as it exhibits two h 5 -bonded cyclopentadienyl groups,m aking it the only neutral aluminumc ompound with this structuralf eature (AlÀ Cp cent :2 04.3-234.1 pm; a:7 2.3-73.98; d:1 43.7-144.98). To that effect,t he formal coordination number of each aluminum atom is eleven.…”
Section: Metallocenophanes Of Group 13 Elementsmentioning
confidence: 99%
“…Binuclear complexes of group 13 elements have been of paramount interest, reflecting not only the fundamental significance of the structural and electronic properties but also their associated potential for exploitation in synthetic chemistry. , Among them, compounds featuring electron-precise Al–Al bonds have attracted considerable attention due to their intriguing reactivity arising from the small bond dissociation energy of Al–Al bonds. , Synthetically, construction of Al–Al bonds is challenging due to the thermal instability and high propensity to undergo disproportionation. Historically, the Uhl’s landmark work in 1988, the first isolation of [(Me 3 Si) 2 HC] 2 Al–Al­[CH­(SiMe 3 ) 2 ] 2 , initiated the synthetic investigations, and a variety of neutral Al–Al derivatives including dialanes(4) R 2 Al–AlR 2 , base-coordinated dialanes(6) LR 2 Al–AlR 2 L (L = Lewis base), , and alumylene-alane adducts R 1 Al→AlR 2 3 , , have been documented so far . Moreover, neutral, monoanionic, , and dianionic compounds exhibiting Al–Al multiple bond character are known in literature.…”
Section: Introductionmentioning
confidence: 99%
“…The first examples of this class of compounds, which was a dicarba‐bridged system reported by Shapiro and coworkers, displayed different hapticities of the cyclopentadienyl groups of η 1 and η 2 , I , II , depending on the coordination environment of the aluminum atom [6a] . Our group recently reported a related disila‐bridged systems with all η 1 σ bonded cyclopentadienyl groups, III , [6b] as well as an imine substituted dicarba‐bridged system with η 1 and η 2 bonded cyclopentadienyl groups, IV , [6c] and a bis(carba[2]aluminocenophane), possessing two η 5 bonded cyclopentadienyl groups on each aluminum atom ‐ the first neutral aluminum compound with such a bonding motif [6c] …”
Section: Introductionmentioning
confidence: 80%